A comparison between two clinically applied plan library strategies in adaptive radiotherapy of bladder cancer. Issue 3 (December 2015) - Tuomikoski, Laura; Valli, Aino; Tenhunen, Mikko; Muren, Ludvig; Vestergaard, Anne
Abstract: Background and purpose: The predominant approach to clinically applied adaptive radiotherapy (ART) for bladder cancer is daily selection of treatment plans from a plan library. In this study we have compared two clinical strategies for creating multiple planning target volumes (PTV) for ART of bladder cancer. Material and methods: Online ART delivering 60 Gy in 30 fractions to the whole bladder was simulated for ten patients using two methods of creating plan libraries. In the RepeatCT method four planning CT scans were acquired at 15-min intervals, generating four CTVs with different bladder volumes. In the RepeatCBCT method one planning CT and four daily cone-beam CT images were combined using Boolean operators to form three composite CTVs. Plan selection rates and PTV volumes were evaluated, with the selected volumes averaged across 30 treatment fractions (PTVmean ). Results: The PTVmean volume was on average 80 cm 3 smaller ( p < 0.001) in the RepeatCT method than in the RepeatCBCT method. Compared to the non-adaptive treatment, the PTVmean was reduced by 46% (range 33–53%, RepeatCT) and 36% (range 27–44%, RepeatCBCT). Conclusions: Both methods reduced the PTVmean volume compared to the non-adaptive approach, but the reduction was larger using the strategy with repeat planning CT imaging. However, the strategy with combined CT and repeat CBCT imaging produced a more adequate range of PTV volumes.